Almost ?r-Statistical and Strongly Almost ?r-Convergence of Order ? of Sequences of Fuzzy Numbers - Isik, Mahmut; Et, Mikail (Hindawi Ltd, 2015)
The main purpose of this article is to introduce the concepts of almost lambda(r)-statistical convergence and strongly almost lambda(r)-convergence of order beta of sequences of fuzzy numbers with respect to an Orlicz function. We give some relations between strongly almost lambda(r)-convergence and almost lambda(r)-statistical convergence of order beta of sequences of fuzzy numbers.
Keywords: Lambda-Statistical Convergence; Difference-Sequences